2020
DOI: 10.1016/j.isci.2020.101385
|View full text |Cite
|
Sign up to set email alerts
|

DOK7 Gene Therapy Enhances Neuromuscular Junction Innervation and Motor Function in Aged Mice

Abstract: Summary Muscle denervation at the neuromuscular junction (NMJ), the essential synapse between motor neuron and skeletal muscle, is associated with age-related motor impairment. Therefore, improving muscle innervation at aged NMJs may be an effective therapeutic strategy for treating the impairment. We previously demonstrated that the muscle protein Dok-7 plays an essential role in NMJ formation, and, indeed, its forced expression in muscle enlarges NMJs. Moreover, therapeutic administration of an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Since the combination of MFGM intake and exercise from a young age has been shown to attenuate the age-related decline in the expression of Dok-7, which promotes NMJ formation [ 22 , 23 , 24 , 32 , 33 ], we examined whether MFGM with exercise from an old age affects the expression of Dok-7. The expression of Dok-7 protein was significantly higher in the Ex-MFGM group than in the Cont group ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the combination of MFGM intake and exercise from a young age has been shown to attenuate the age-related decline in the expression of Dok-7, which promotes NMJ formation [ 22 , 23 , 24 , 32 , 33 ], we examined whether MFGM with exercise from an old age affects the expression of Dok-7. The expression of Dok-7 protein was significantly higher in the Ex-MFGM group than in the Cont group ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, in the current study MFGM supplementation increased the protein expression of Dok-7 in muscles, which is consistent with the results of our previous studies [ 20 , 22 ]. We recently showed that the overexpression of Dok-7 in skeletal muscles ameliorated age-related NMJ denervation [ 32 ], and therefore MFGM may have secondary effects on the nervous system via muscles and NMJs. Further studies are needed to clarify whether MFGM directly affects the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the soleus muscle was used to observe the muscle's detailed structure. This method is widely used to determine muscle structure in animal models (Zeller‐Plumhoff et al, 2017), and to determine the degree of damage and recovery of sensorimotor function through functional evaluation in animal models (Ueta et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…NMJ fragmentation and denervation, and consequent decreased skeletal muscle contractility in aging skeletal muscle have also been mitigated by stabilizing endplates: for example, via transgenic expression of LRP-4 and α-sarcoglycan (which delays LRP-4 degradation). Gene therapy to increase expression of Dok-7 (a cytoplasmic adapter protein, which is a substrate of MuSK and activates MuSK kinase activity) [ 144 ] in aging skeletal muscle also improves the acetylcholine receptor area, innervation and consequent skeletal muscle contractility, further implicating the role of NMJ pathology in sarcopenia [ 145 , 146 ]. An engineered agrin (a C-terminal fragment of mouse agrin) improved skeletal muscle strength in a sarcopenia-like murine muscle model (neurotrypsin-overexpression) [ 147 ].…”
Section: Therapeutic Approaches To Nmj Functionmentioning
confidence: 99%